Upaya Polres Bojonegoro dalam Meminimalisir Konflik antar Perguruan Pencak Silat Menurut Undang-Undang Nomor 2 Tahun 2002 ( Studi Kasus Di Wilayah Hukum Polres Bojonegoro) - Gangga Listiawan; Abd. Hadi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Efforts, Bojonegoro Police, Minimizing, Conflict, Pencak Silat College, Law No. 2 of 2002 Society is a group of people who live together and work together to achieve certain goals. The aim of establishing the Bojonegoro village of martial arts is to collaborate with all the pencak silat school groups in Bojonegoro, and become community security partners to be able to assist the National Police in maintaining a stable security situation and condition so that people feel safe. Based on the above, it creates problems, what are the duties and powers of the police according to law number 2 of 2002, and how are the efforts of the Bojonegoro Police in minimizing conflicts between pencak silat colleges in Bojonegoro in accordance with article 5 paragraph 1 of law number 2 of 2002. The type of research that researchers use is empirical normative qualitative research. The data sources used are primary data, secondary data. The research instruments used were observation, interviews, documentation. while the data analysis technique used is data reduction, data presentation, to draw conclusions and verification. The results of this study are that the Police are responsible for creating an atmosphere of order and security in society, and for implementation in an effort to create security and order it is fully handed over to the Police and the police have the right to use preventive methods as a form of prevention or in a repressive way. Second, in an effort to minimize this conflict, the police formed the Bojonegoro Kampung Pesilat (BKP) and often visited university heads to provide ideas for the importance of creating peace and order in society.